Failure analysis of the fasten system of wheels used in mining pickup trucks. (April 2017) - Artigas, A.; Monsalve, A.; Colás, R.; Garza-Montes-de-Oca, N.F.
Highlights: Deficient torque practices lead to plastic deformation of lug nuts and wheel ejection. Gap formation in machine elements promotes fatigue of bolts. Local decarburization promotes crack formation in high strength bolts. Abstract: Regardless of their specific applications, all the vehicles used in mining operations are subjected to severe working conditions that reduce in a considerable amount, their active in-service life. In this work, the causes that promote failure of the fasten system and subsequent ejection of the wheels of passenger pickup trucks used in open-pit mines are analysed. By means of scanning electron microscopy, optical microscopy analyses and hardness tests, it was found that failure of the fasten system is characterised by a series of synergetic steps that include, the plastic deformation of the lug nuts caused by deficient tightening practices, fatigue and plastic deformation of the bolts. When combined, these phenomena leaded to the formation of cracks that propagated in the radial direction of these elements. The reasons that promote the development of this kind of failure are presented and discussed in this investigation.